Peningkatan Motivasi Kewirausahaan dan Pengelolaan Keuangan pada Siswa SMA Negeri 1 Berastagi - Yunita Eriyanti Pakpahan; Cristnova Hasugian; Maria Damenta Iren Warat; Yanita Manda Sari; Jefrin anugrah (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Students as intermediaries giving influence in the household have a very important role in the family and even on society. The role and contributionof students is an important factor in facing various challenges in recovery efforts, family economy. Therefore, it is important to provide insight to students in economics. In encouraging the recovery of Indonesia’s future creative economy. One of thr solutions to family economic problems through studens is by providing students with insight to transfer knowledge to families, which are able to generate money that icreases family income, one of which is by motivating and increasing entrepreneurship education, of course it will open up insights to open businesses generated through families and managing money that is Good. Therefore, motivation is carried out for SMA Negeri 1 Berastagi School Students, equipping and motivating them to open businesses that are able to help family finances. This activity will be carried out on January 27 2023 at the Multimedia Building of SMAN 1 Berastagi. This activity will prduce output publications in online mass media/service journals. Intense communication will also be carried out between the nedds of the scholl and students who will open a business to follow up on the results of the educations received. Keywords : Motivation, Entrepreneurship, Managemen